Stock market and growth in Greece: evidence from cointegration and causality tests - Αντωνάκης, Νικόλας; Αποστόλου, Απόστολος (SPOUDAI Journal of Economics and Business, 1999)
Current wisdom suggests that stock-market development may affect economic growth by raising the proportion of savings funnelled to investment and/or increasing the social marginal productivity of capital and/or influencing the saving rate. Earlier empirical studies on the subject, however, have reported conflicting research findings, attributable to the use of cross-sectional data and differences in the samples chosen, time periods examined and data bases used. Moreover, the evidence suggests that the causal link between finance and growth is crucially determined by the nature and operation of the financial institutions and policies pursued in each country. These considerations point to the need for case specific studies using time-series data for individual countries. In this context, the present study seeks to contribute to current research in the area by investigating the relationship between economic growth and stock-market activity in the case of Greece over the period 1958-95. To this end, an endogenous growth model is specified providing a formal rationalization for the incorporation of stock-market activity in a sources — of — growth equation. Using cointegration and causality tests, the paper reports findings that provide empirical support to the hypothesis that stock-market development does not affect positively the output growth rate in Greece.